Form, Content, and Meaning in Lev 24:10–23: A Diachronic Analysis - Amar, Itzhak (Journal of Hebrew Scriptures, 2025)
The narrative of the blasphemer (Lev 24:10–23)—the only narrative segment within the Holiness Code (Lev 17–26)—has long been a subject of scholarly debate. Discussions have primarily focused on issues of textual coherence and thematic connections, such as the link between the prohibition against desecrating God's name and the subsequent inclusion of case laws that align with the principle of lex talionis (the law of retaliation). In this article, I aim to address the complex questions raised by this passage and propose that it should be understood as a cohesive unit consisting of two sequential stages. The arrangement of these stages not only emphasizes their inherent connections but also sheds light on the underlying rationale that shapes the structure and purpose of this narrative unit.